Skill mismatch : the role of the enterprise - (:unkn) unknown (Publications Office of the European Union, 2012)
"Understanding the dynamics of skill mismatch is a crucial pillar of Cedefop's work on skills in the European labour market. While most research to date has focused on the individual perspective, this report is a first attempt to explore the role of enterprises in mitigating skill mismatch. Specific attention is given to the potential role of human resource practices (e.g. recruitment, training, performance appraisal and pay-setting, job design, employee empowerment) and of high performance workplaces for ensuring that the knowledge, skills and competences of individuals are used to best effect. The report paves the way for a closer look into what has previously been a black box of the skill mismatch agenda: what is the role of the firm in anticipating and matching skill needs with skill supply within a fast-paced and uncertain economic environment?" (Hrsg., BIBB-Doku)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; S 5.3 Personalentwicklung; S 1.5.3 Betriebliche Weiterbildung; G 1.2.2.1 Lohn- & Tarifsysteme; G 2.3.1 Arbeitsteilung & -organisation; I 2.2 Europa; Berufliche Qualifikation; Qualifikationsbedarf; Mismatch; Unternehmen; Personalpolitik; Personalgewinnung; Betriebliche Weiterbildung; Lohnpolitik; Leistungsanreiz; Arbeitsgestaltung; Arbeitnehmerbeteiligung; Arbeitnehmervertretung; Europa